2021
DOI: 10.3390/molecules26123681
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Brewing Process Parameters on Antioxidant Activity and Caffeine Content in Infusions of Roasted and Unroasted Arabica Coffee Beans Originated from Different Countries

Abstract: Coffee is one of the most often consumed beverages almost all over the world. The multiplicity of beans, as well as the methods and parameters used to brew, encourages the optimization of the brewing process. The study aimed to analyze the effect of roasting beans, the brewing technique, and its parameters (time and water temperature) on antioxidant activity (determined using several in vitro methods), total polyphenols, flavonoids, and caffeine content. The infusions of unroasted and roasted Arabica beans fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 46 publications
6
28
0
Order By: Relevance
“…It showed that roasting degree and brewing method—compared with other parameters—were the most discriminating factors based on UV and fluorescence spectra of coffee brew samples, respectively. On the contrary, Muzykiewicz-Szymańska et al [ 25 ] studied the effect of brewing process parameters on antioxidant activity in infusions of roasted and unroasted Arabica coffee beans originating from different countries. They concluded that the phenolic compound content in infusions prepared using different techniques depended on the roasting process, the bean’s origin, as well as the brewing technique.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that roasting degree and brewing method—compared with other parameters—were the most discriminating factors based on UV and fluorescence spectra of coffee brew samples, respectively. On the contrary, Muzykiewicz-Szymańska et al [ 25 ] studied the effect of brewing process parameters on antioxidant activity in infusions of roasted and unroasted Arabica coffee beans originating from different countries. They concluded that the phenolic compound content in infusions prepared using different techniques depended on the roasting process, the bean’s origin, as well as the brewing technique.…”
Section: Discussionmentioning
confidence: 99%
“…The reason that the intervention with blended coffee increased blood lipids could be attributed to caffeine. Robusta coffee species contain more caffeine than Arabica [ 18 , 19 , 53 ]. It has been previously shown, in vitro and in vivo using animal models, that caffeine supplementation increased hepatic cholesterol synthesis and serum cholesterol due to reduced incorporation of fatty acids and sterols in the liver [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coffee extraction is the final step in coffee production and has a great influence on the final form and properties of the beverage. Generally, coffee brewing techniques can be divided into high- and low-temperature processes 6 8 . The most popular methods of hot coffee brewing include the Turkish technique, espresso, filtered (V60, Aeropress, French Press) and simple infusion method 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, coffee brewing techniques can be divided into high- and low-temperature processes 6 8 . The most popular methods of hot coffee brewing include the Turkish technique, espresso, filtered (V60, Aeropress, French Press) and simple infusion method 8 , 9 . Turkish coffee is prepared by boiling the coffee in water, while a simple infusion is based on combining the ground grains with hot water (85–96 °C) and macerating for approximately 3–5 min 6 , 8 .…”
Section: Introductionmentioning
confidence: 99%